PROSES PENYIDIKAN PERKARA TINDAK PIDANA NARKOTIKA (STUDI KASUS SAT RES NARKOBA POLRESTA SURAKARTA) - Rika Romadzoni; Amir Junaidi; Hafid Zakariya (Wajah Hukum, 2018)
The purpose of this research is to know the process of the implementation of the investigation against the crime of narcotics in a drug Polresta Surakarta Reskrim Units and to know the obstacles faced by Police investigators in conducting the process of investigation the Crime Unit in the Narcotics Drug Reskrim Polresta Surakarta. Research methods used are empirical juridical. Based on the results of research and analysis of the data it can be concluded that the process of case investigation of narcotics crime in Drug Polresta Surakarta Reskrim Units namely (1) received a report (2) the first Action after receiving a report from the someone then the investigators conducted a series of investigations and pembuntutan against someone suspected of (3)(4) Arrest Search Seizure (5) (6) the examination of the suspect and Witness Detention (7) (8) the completion of the Investigation. Obstacles in by investigators in conducting investigation is many people who don't want to inform the user about the Narcotics to the police.Key Words: Process, Investigators, Narcotics.